Long-acting antiretroviral therapy effectiveness and patient satisfaction using patient questionnaires: data from a real-world setting - Konishi, Keiji; Onozuka, Daisuke; Okubo, Moeka; Kasamatsu, Yu; Kutsuna, Satoshi; Shirano, Michinori (BMC infectious diseases, 2024)
Background Antiretroviral therapy (ART) for HIV infection has evolved substantially. The development of long-acting drugs, such as cabotegravir (CAB) and rilpivirine (RPV) might improve treatment satisfaction among people living with HIV (PLWH). The real-world effectiveness of long-acting ART and its effect on patient satisfaction needs to be assessed. This study investigated antiviral effectiveness and treatment satisfaction in PLWH who switched from conventional to long-acting ART (CAB + RPV). Methods This prospective cohort study included PLWH aged 18 years and older who switched to CAB + RPV and received the injections every 8 weeks between June 2022 and May 2023, after a 4-week oral lead-in phase. The eligibility criteria included viral suppression, absence of hepatitis B virus (HBV) DNA, and no prior RPV resistance mutations. Clinical data, including renal, lipid, and glucose biomarker levels, were monitored from the baseline to 44 weeks after switching. Treatment satisfaction was assessed using the HIV Treatment Satisfaction Questionnaire. A linear mixed-effects model was used to estimate changes in clinical data from baseline. Results Thirty-eight male participants were enrolled. Some participants had detectable levels of viral replication; however, all participants maintained viral suppression (HIV-RNA < 50 copies/mL) at 44 weeks and no cases of virological failure were detected. The creatinine level decreased by − 0.04 mg/dL (95% confidence interval [CI]: − 0.07 to − 0.01), lipid and glucose profiles remained stable, and treatment satisfaction increased by 6.6 points (95% CI: 2.4 to 10.8) after switching to CAB + RPV. Conclusions Long-acting ART provides effective viral suppression and enhances treatment satisfaction in PLWH switching from conventional ART. Long-acting ART can improve patient well-being; however, patient selection and monitoring to prevent HBV-related complications are important.